118 A retrospective study of the growth in comorbidity diagnoses in paediatric inpatients. (23rd February 2023) - Bowyer, Stuart A; Pissaridou, Eleni; Booth, John; Briggs, Lydia; Bryant, William A; Key, Daniel; Shah, Mohsin; Spiridou, Anastassia; Sebire, Neil J
Abstract : Introduction: Diagnoses are a key aspect of the Electronic Health Record (EHR) that patients acquire at a healthcare provider. In addition to directing an individual patient's care, diagnosis data is used in clinical, operational, and public health research. While some patients have single diagnoses, many have comorbidities/multimorbidities that are stored in the clinical record. We performed a retrospective study of the number of concomitant diagnoses in paediatric inpatients to understand if and how this has changed over time. Method: We extracted hospital encounter diagnoses and admissions for patients with an overnight inpatient admission at the Great Ormond Street Hospital (GOSH) between January 2000 and December 2021 from the Epic and legacy EHRs. Diagnoses were coded using ICD-10 and de-identified by the GOSH Digital Research Environment. Diagnoses were matched to corresponding admissions and two metrics were calculated on an annual basis. (a) The mean number of simultaneously recorded unique concomitant diagnoses per patient entry and (b) The mean number of unique diagnoses recorded per patient admission. All analysis was performed in R. Results: Based on 111, 784 patients and 2, 305, 216 diagnosis instances, there has been a large increase in both metrics of concomitant diagnoses between 2000 and 2021. The mean number of unique diagnoses per entry rose from 2.8 in the year 2000, to 12.5 in 2021. The mean number of unique diagnoses per admission rose from 2.9 in 2000 to 12.6 in 2021. Discussion: These results illustrate that there has been a large increase in the recording rate of diagnoses since the year 2000 in the GOSH EHR. This is an important consideration for any secondary data use, as analyses based on historical diagnoses may no longer be valid. Further study is required to control for changes in diagnosis complexity and reporting guidelines to verify the implications of these findings.